Antifibrotic Mechanism of Piceatannol in Bleomycin-Induced Pulmonary Fibrosis in Mice - Sheng, Hanjing; Lin, Gang; Zhao, Shengxian; Li, Weibin; Zhang, Zhaolin; Zhang, Weidong; Yun, Li; Yan, Xiaoyang; Hu, Hongyu (Frontiers in Pharmacology, 2022)
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial lung disease characterized by myofibroblast accumulation and extracellular matrix deposition, which lead to irreversible damage of the lung’s architecture and the formation of fibrotic lesions. IPF is also a sequela in serious patients with the coronavirus disease 2019 (COVID-19). The molecular mechanisms under pulmonary fibrosis remain unclear, and there is no satisfactory treatment currently available. Piceatannol (PIC) is a naturally occurring resveratrol analog found in a variety of dietary sources such as grapes, passion fruit, and white tea. It has been reported to inhibit liver fibroblast growth and exhibited various antitumor activities, although its role in pulmonary fibrosis has not been established yet. In the present study, we evaluated the anti-fibrotic role of PIC in bleomycin (BLM)-induced pulmonary fibrosis in mice. Methods: Mice with BLM-induced pulmonary fibrosis were treated with PIC, and fibrotic changes were measured by hematoxylin-eosin (H&E) staining and hydroxyproline assay. Luciferase assay, Western blot assay, histological analysis, and immunofluorescence staining were used to evaluate the effect of PIC on fibroblast activation and autophagy in mouse embryonic fibroblast cells (NIH-3T3) and human lung fibroblast cells (HFL1). The anti-fibrotic mechanisms of PIC were either confirmed in vivo. Results: Our results showed that PIC significantly alleviated the bleomycin-induced collagen deposition and myofibroblast accumulation. In vitro and in vivo studies indicated that PIC plays a role in activating autophagy in the process of anti-fibroblast activation. Further mechanism studies demonstrated that PIC can promote autophagy via inhibiting the TGF-β1-Smad3/ERK/P38 signaling pathway, which leads to a decreased number of activated myofibroblasts. Conclusion: Our study demonstrated for the first time that PIC possesses the protective effects against bleomycin-induced pulmonary fibrosis due to the direct pulmonary protective effects which enhance the effect of autophagy in vitro and in vivo and finally leads to the decreased number of activated myofibroblasts. PIC may serve as a candidate compound for pulmonary fibrosis therapy and attenuates the sequelae of SARS-COV-2 pulmonary fibrosis.